2010
DOI: 10.1021/jp1055123
|View full text |Cite
|
Sign up to set email alerts
|

A Solid-State 17O NMR Study of l-Tyrosine in Different Ionization States: Implications for Probing Tyrosine Side Chains in Proteins

Abstract: We report experimental characterization of (17)O quadrupole coupling (QC) and chemical shift (CS) tensors for the phenolic oxygen in three l-tyrosine (l-Tyr) compounds: l-Tyr, l-Tyr.HCl, and Na(2)(l-Tyr). This is the first time that these fundamental (17)O NMR tensors are completely determined for phenolic oxygens in different ionization states. We find that, while the (17)O QC tensor changes very little upon phenol ionization, the (17)O CS tensor displays a remarkable sensitivity. In particular, the isotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 84 publications
5
28
0
Order By: Relevance
“…GIPAW calculations and NMR experiments of the crystalline solid (non-DNP) at higher magnetic fields (Table 2, Figure S4) agree well with experimental parameters as well as other phenolic-like systems studied previously. 100, 140 …”
Section: Resultsmentioning
confidence: 99%
“…GIPAW calculations and NMR experiments of the crystalline solid (non-DNP) at higher magnetic fields (Table 2, Figure S4) agree well with experimental parameters as well as other phenolic-like systems studied previously. 100, 140 …”
Section: Resultsmentioning
confidence: 99%
“…A similar "␦ 11 -␦ 22 crossover" effect was previously reported for the phenolic oxygen atom of tyrosine between the protonated and deprotonated states. 64 To further identify the origin of the observed 17 O coordination shift in terms of specific molecular orbitals (MOs), we performed a detailed magnetic shielding analysis using the ADF program. 46 According to the Ramsey formalism of nuclear magnetic shielding, 65 the total magnetic shielding at a nucleus can be divided into diamagnetic and paramagnetic contributions:…”
Section: The Origin Of 17 O Coordination Shiftsmentioning
confidence: 99%
“…56,57,64,67 that the high-lying nonbonding orbitals (electron lone pairs) on the oxygen atom often make the largest paramagnetic shielding contribution. Use oxaliplatin as an example.…”
Section: The Origin Of 17 O Coordination Shiftsmentioning
confidence: 99%
“…The paramagnetic term, on the other hand, gives rise to the anisotropic components of shielding and originates from the interaction between the ground and excited state wavefunctions. Previous reports have demonstrated that the paramagnetic shielding of carbon- and nitrogen- bound 17 O nuclei originates from oxygen lone pair electrons that occupy high-energy orbitals [4649]. However, the orientation of the largest component of chemical shift tensor along the V-O bond in HS003 indicates the participation of vanadium orbitals in the paramagnetic shielding of the peroxido oxygens.…”
Section: Resultsmentioning
confidence: 99%